2018
DOI: 10.1061/(asce)me.1943-5479.0000579
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Social Network Analysis Applications in Complex Project Management

Abstract: Social Network Analysis (SNA) is a significant tool for analyzing networks in complex project management that examines the actors' interdependence in iterative and interactive social structures. It can also be used for non-social structure analysis. The potential of SNA could be extended significantly if its application to complex project management could be clarified. The objectives of the present review are threefold: (1) to clarify the interpretation of SNA metrics; (2) to identify its applications to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 144 publications
0
86
0
1
Order By: Relevance
“…Although the study has successfully shown the mediating effects of interorganizational trust and distrust in the relationship between joint-contract functions and BIM-enabled EPC project performance, future studies should determine how contract functions influence trust among project stakeholders through a comprehensive social network analysis. Through investigating formal and informal collaborative relationships using social network analysis, researchers could assess the dynamic evolution of interorganizational trust among project participants during BIM-enabled project implementation (Lee et al 2017).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Although the study has successfully shown the mediating effects of interorganizational trust and distrust in the relationship between joint-contract functions and BIM-enabled EPC project performance, future studies should determine how contract functions influence trust among project stakeholders through a comprehensive social network analysis. Through investigating formal and informal collaborative relationships using social network analysis, researchers could assess the dynamic evolution of interorganizational trust among project participants during BIM-enabled project implementation (Lee et al 2017).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…The popularity of this review approach has extended to a range of disciplines including software engineering (Kitchenham et al, 2009), information systems (Rowe, 2014), organizational (Birkinshaw and Gupta, 2013), and general management studies (Crossan and Apaydin, 2010). More recently, systematic reviews have become popular in not only operations management (Thome et al, 2016;Maestrini et al, 2017), but also project management (Xue et al, 2010;Stingl and Geraldi, 2017;Lee et al, 2018). Systematic reviews of literature are defined by Rowe (2014),drawn from Kitchenham et al (2009) as "…a form of secondary study that uses a well defined methodology to identify, analyse and interpret all available evidence related to a specific research question in a way that is unbiased and (to a degree) repeatable" (p. 246).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…SNA is useful methodology for understanding the social phenomenon and social structure that Moreno started with the term "Sociometry" [5]. It has been used in not only social science research but also construction research such as communication management, stakeholder management and procurement management [2]. By using SNA, it is possible to analyze the network connecting the actor called node to the line called tie, and graphically shows the relationship or flow between the nodes by showing the given data with nodes and links.…”
Section: Social Network Analysismentioning
confidence: 99%